2013
DOI: 10.1016/j.eneco.2013.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Selective hedging in hydro-based electricity companies

Abstract: We analyze risk management trends in electricity commodity markets using the production and transaction data and written hedging policies of 12 Norwegian hydropower companies. The scope of our analysis is the hedging of physical electricity production using the power derivatives available at NASDAQ OMX Commodities. In their hedging policy, these companies either use a Cashflow at Risk (C-FaR) approach or a hedge ratio approach, or follow no explicitly stated approach. We find that the derivative cashflows cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Leoni et al (2013) investigate hedging strategies for the energy derivatives. Sanda et al (2013) analyse the risk management trends in the electricity commodity markets.…”
mentioning
confidence: 99%
“…Leoni et al (2013) investigate hedging strategies for the energy derivatives. Sanda et al (2013) analyse the risk management trends in the electricity commodity markets.…”
mentioning
confidence: 99%
“…Lohman and Hildyard (2014) explain this as the increasing commodification of uncertainty through hedging mechanisms as a means of estimating the cost of risks. Sanda et al (2013) revealed in a study of 12 Norway hydropower utilities that their hedging policy strategies were a source of significant profit. In other words, higher risks generate higher potential profits, rather than benefits.…”
Section: Explain How Neoliberal Policy Reform Facilitated Thismentioning
confidence: 99%
“…Using an OLS model and a moving window to allow for time variation, he documents relatively poor performance using a measure based on accumulated gain but notes that this may relate to ambiguity about the goals of a hedging strategy whereby risk minimisation may not be the main objective. More recently, Sanda, Olsen, & Fleten, () look at company level hedging for hydro‐based electricity companies and find that over 90% of aggregate production is hedged. They use cash flow at risk rather than the variance as their measure of hedging efficacy and find that only 1 of 12 companies showed a significant reduction in monthly cash flow variance.…”
Section: Introductionmentioning
confidence: 99%